Serological evidence of West Nile virus in wild birds in Portugal - Loureiro, Filipa (2024)
West Nile Virus (WNV) has a zoonotic transmission cycle. Avian species are considered the definitive hosts, and mosquitoes and other arthropods are the main vectors. Humans are considered accidental and dead-end hosts, since mammals are unable to efficiently amplify the virus. We aimed at studying serological prevalence of WNV circulation in wild birds in Portugal.